Change in Texture of Enamel when Subjected to Arabica Coffee - Basilio; O. , Nestine Angelo; Esguerra; A. , Paula Edraline; Vicmudo; I. , Kricia Ann; Ziganay; P. , Ericson; S. Wong, Shirley (International Journal of Psychosocial Rehabilitation, 2020)
Aim: To determine the change in texture of the enamel of the freshly extracted teeth when subjected to Arabica coffee. Materials and Method: Six recently extracted teeth with no carious or pathologic lesion from patients undergoing orthodontic treatment whose first premolars are needed to be extracted due to crowding and are soaked in saline solution will be used for this study. A random tooth will be utilized for the study of any texture, analyzing the morphology of a tooth using SEM (scanning electron microscopy). Result: After soaking the six specimens in Arabica coffee, the researchers observed each tooth clinically. Out of six specimens, five of them had changed in texture of enamel. This data proves that the acidity of the said coffee really affects the surface of the tooth. The researchers also observed that the root portion of the tooth had more roughness than the crown portion. The researchers proved that coffee can roughen the tooth surface with the help of scanning electron microscopy (SEM), which they have used to view it microscopically.